The Phenomenon of Islamophobia in Germany on Indonesian Online News Sites 2018-2023 - Balkis Nur Azizah; Abdul Muntaqim Al Anshory; Adul Leesen (Fenomena)
Islamophobia does not only occur among non-Muslims but Islamophobia is also experienced by Muslims who do not agree with their thoughts. Islamophobia is a psychological symptom that sufferers experience when they encounter Muslims. The cause could be due to an unpleasant experience experienced by the sufferer, or because they are influenced by news reporting that Islam is a harsh religion, so that they feel afraid if they must face Muslims. The aims of this research are (1) to understand the picture of Islamophobia in Germany; (2) analyze the form of Islamophobia in Germany; and (3) describe the impact of Islamophobia in Germany. Researchers used descriptive qualitative methods with primary data sources in the form of online news and supported by related journals as secondary data. The results of the research are (1) Symptoms of Islamophobia in Germany have increased significantly every year; (2) the forms of Islamophobia found were the dissolution of mosques, harassment of Muslim women and prohibitions on wearing the headscarf, public opinion, work and education; (3) the impact of Islamophobia in Germany, namely psychological, social, legal and political policies.